2011
DOI: 10.4315/0362-028x.jfp-10-316
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Listeria monocytogenes In Vitro through the Combination of Octanoic Acid and Acidic Calcium Sulfate

Abstract: It has been hypothesized that inhibition of foodborne pathogens can be enhanced by using antimicrobials in combination. A broth dilution assay was devised to determine whether inhibition of Listeria monocytogenes exposed to the combination of the fatty acid octanoic acid (OCT) and the organic acid-containing antimicrobial acidic calcium sulfate (ACS) was enhanced compared with the inhibition of the pathogen exposed to either antimicrobial applied singly. MICs for OCT and ACS were 25.00 μg/g and 1.56 ml/liter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Our work mainly intended to evaluate the listericidal action by relatively new GRAS antimicrobials, such as phage P100 and LAE that were not been tested previously for their effectiveness against L. monocytogenes in CSS. In food industry, use of multihurdle approach that relies on more than one antimicrobial agent or combining antimicrobial agents with some form of physical inactivation treatment is becoming quite common (Ananou et al, 2010;Brandt et al, 2011). There are several reasons for shifts towards multihurdle approach to control foodborne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Our work mainly intended to evaluate the listericidal action by relatively new GRAS antimicrobials, such as phage P100 and LAE that were not been tested previously for their effectiveness against L. monocytogenes in CSS. In food industry, use of multihurdle approach that relies on more than one antimicrobial agent or combining antimicrobial agents with some form of physical inactivation treatment is becoming quite common (Ananou et al, 2010;Brandt et al, 2011). There are several reasons for shifts towards multihurdle approach to control foodborne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Octanoic acid is commercially available (Octa-Gone™) and has been shown to reduce L. monocytogenes by as much as 3.34 log CFU/sample for cured ham (Burnett et al, 2007). Octanoic acid has been observed to provide a synergistic effect on inhibition of L. monocytogenes when combined with acidic calcium sulfate (Brandt et al, 2011). However, none of the combinations tested produced bactericidal effects on L. monocytogenes.…”
Section: Ingredients and Antimicrobial Compoundsmentioning
confidence: 96%
“…The inhibition of foodborne pathogens can be enhanced by using antimicrobials in combination. In this regard, Brandt et al (2011) conducted a study to estimate the effects of octanoic acid (OCT) and acidic calcium sulfate (ACS) on inhibition of Listeria monocytogenes. The results indicated that this ombination enhanced the inhibition of pathogen.…”
Section: Acidic Calcium Sulfatementioning
confidence: 99%